Fibrodysplasia Ossificans Progressive Two Forms of a Disease - Y Aghighi,; F Abolnejadian,; SR Raeiskarami; V Ziaee (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2010)
BACKGROUND AND OBJECTIVE: Fibrodysplasia ossificans progressive (FOP) or myositis ossificans progressiva is a rare hereditary connective tissue disorder. Diagnosis can be made by the typical clinical features (congenital malformations of the great toes and hallux valgus deformity) and ectopic ossification. Early diagnosis can lead to avoidance of additional harmful diagnostic and treatment procedures (such as injection and biopsy) and trauma prevention. In this report we present 2 typical cases of FOP with early and delay diagnosis.CASE: The first case was an 11 year-old girl. The first symptom was painless nodule on the skull at 2.9 years old. She had congenital malformations of the great toe and hallux valgus deformity in both feet. According to clinical findings, the diagnosis was confirmed at 3 years. She was on etidronate and she had regular follow-up every 6 months. Now, she had no any disability. The second case was a 12 year-old boy. He had had a neck mass at 18 months and he was repeatedly visited by different physicians and some unnecessary tests and procedures were done for him, but the diagnosis had a delay until 8 years old, when he referred to our pediatric rheumatology clinic. He had hallux valgus deformity and congenital malformations of the great toe in both feet. Several ectopic ossifications had occurred in abdomen wall, upper and lower limbs. Now, he walks but he cannot sit.CONCLUSION: Because tissue damage serves as a focus for ossification, early diagnosis can protect the patient from trauma and avoidance of unnecessary procedures.